2017
DOI: 10.1055/s-0036-1588453
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric [3+3] Cycloaddition for Heterocycle Synthesis

Abstract: Asymmetric syntheses of six-membered ring heterocycles are important research targets not only in synthetic organic chemistry but also in pharmaceuticals. The [3+3]-cycloaddition methodology is a complementary strategy to [4+2] cycloaddition for the synthesis of heterocyclic compounds. Recent progress in [3+3]-cycloaddition processes provide powerful asymmetric methodologies for the construction of six-membered ring heterocycles with one to three heteroatoms in the ring. In this account, synthetic efforts duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Because of their inherent stability, nitrones are popular for catalytic dipolar cycloaddition transformations. 4b, [10][11][12][13]42 In previous investigations of nitrone cycloaddition reactions with enoldiazoacetates, copper(I) catalysis was not as effective or selective as catalysis by chiral rhodium(II) carboxylates 43 or silver(I)/t-BuBOX. 44 However, reinvestigation of this process revealed that enoldiazocarbonyl compounds and enoldiazosulfones offered consistently higher yields and enantioselectivities under copper(I) catalysis [39][40][41] than did the corresponding enoldiazoacetates under rhodium(II) catalysis.…”
Section: Asymmetric [3+3]-cycloaddition 41 Nitronesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their inherent stability, nitrones are popular for catalytic dipolar cycloaddition transformations. 4b, [10][11][12][13]42 In previous investigations of nitrone cycloaddition reactions with enoldiazoacetates, copper(I) catalysis was not as effective or selective as catalysis by chiral rhodium(II) carboxylates 43 or silver(I)/t-BuBOX. 44 However, reinvestigation of this process revealed that enoldiazocarbonyl compounds and enoldiazosulfones offered consistently higher yields and enantioselectivities under copper(I) catalysis [39][40][41] than did the corresponding enoldiazoacetates under rhodium(II) catalysis.…”
Section: Asymmetric [3+3]-cycloaddition 41 Nitronesmentioning
confidence: 99%
“…Recently the transition metal catalyzed vinylcarbene approach to cycloaddition has shown considerable promise for highly chemo-, regio-, and enantio-selective cycloaddition reactions. Examples of [3+4]-, 9 [3+3]-, [10][11][12][13][14] [3+2]-, [14][15][16][17][18][19][20] and even a [3+1]- 21 and [3+5]- 22 cycloaddition reactions have been reported using dipolar metallo-vinylcarbenes, generally in high yields with low catalyst loadings. The transformations of silyl-protected enoldiazo compounds (Scheme 2) involve initial nucleophilic attachment to the electrophilic vinylogous position of the metallo-vinylcarbene followed by electrophilic addition to the original carbenic center with displacement of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 A number of powerful synthetic methods have been developed based on these versatile reagents, especially their use as three-carbon building blocks to access various carbo-or heterocyclic frameworks via metal-catalyzed [3C + n] cycloadditions (n = 1-5). [32][33][34][35][36] Most methods rely on the initial formation of electrophilic metal carbene intermediates through a diazo decomposition. By contrast, the development of new reactions triggered by their alkene motif is still challenging because many of the vinyldiazo reagents are prone to 1,5-electrocyclization to form pyrazoles if the diazo functionality cannot be rapidly decomposed.…”
Section: Introductionmentioning
confidence: 99%
“…Cycloaddition reactions have a long held and privileged position in synthetic organic chemistry. , Their applications enable the synthesis of carbocyclic and heterocyclic compounds by processes that are concerted or stepwise, and they involve the combination of m atoms with n atoms to provide a cyclic array of ( m + n ) atoms, where m and n are integers. For the synthesis of six-membered ring compounds, the [4 + 2]-cyclization has been the most used methodology, , but recently, [3 + 3]-cycloaddition has offered a highly selective alternative . The transition metal catalyzed [3 + 3]-cycloaddition of enoldiazoacetates introduced for the first time in 2011 has provided high yields and good to excellent enantiocontrol in reactions with a wide variety of dipolar reagents that occur under mild conditions using dirhodium carboxylate catalysts (Scheme ).…”
Section: Introductionmentioning
confidence: 99%